Cerebral lesions in the central pain matrix are associated with headache in multiple sclerosis - Fröhlich, Kilian; Macha, Kosmas; Siedler, Gabriela; Sekita, Alexander; Haupenthal, David; Mrochen, Anne; Wang, Ruihao; Schembs, Leah; Dörfler, Arnd; Seifert, Frank; Schwab, Stefan; Winder, Klemens (Scientific Reports, 2025)
Headache is very frequent in multiple sclerosis. However, the question whether headache is just coincidental or may be secondary due to inflammatory cerebral multiple sclerosis lesions is yet to be clarified. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in patients with multiple sclerosis and comorbid headache using voxel-based lesion symptom mapping (VLSM). Patients with multiple sclerosis and headache were prospectively identified and included in a university neurological center between 2017 and 2023. Only patients with headache onset after first manifestation of multiple sclerosis were included. Demographic and clinical data were assessed, and lesion volumes calculated. Cerebral lesion sites were correlated voxel-wise with presence and absence of headache using non-parametric permutation testing. A cohort of multiple sclerosis patients served as controls for the VLSM-analysis. 48 multiple sclerosis patients with headache were included, as well as 92 controls without headache. Of the 48 patients with headache, 39 (81%) were female and nine (19%) were male. Mean age was significantly higher in headache patients than in controls (51 + / − 11 vs. 42 + / − 11 years, p < 0.05). EDSS, disease duration and lesion volumes did not significantly differ between both groups. Lesion overlap of all patients demonstrated a distribution of white matter lesions consistently in all subcortical brain areas. The VLSM-analysis showed associations between headache and lesion clusters in the left insula, left hippocampus and right thalamus. In our study, multiple sclerosis lesions in the left insula, left hippocampus and right thalamus were associated with headache in multiple sclerosis patients. The data therefore indicates that headache in multiple sclerosis may, in a proportion of patients, result from lesions in the central nervous systems’ pain processing network. Trial registration: No. 93_17 B, Ethics committee of the University Hospital Erlangen-Nürnberg.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cerebral lesions; Headache; Multiple sclerosis; Voxel-based lesion symptom mapping